Sympathetic intervention in abdominopelvic cancer pain: A systematic review and meta-analysis - Made Agus Mahendra Inggas; Fandi Hendrawan; Amelia Marcelina; Kezia Aurelia Tamzil; Takaomi Taira (World Neurosurgery: X)
This review aims to investigate the effectiveness of CP, SHP, and GI intervention as a singular or combination to reduce the pain intensity. Medline, Scopus, and CENTRAL databases were used to identify abstracts using predefined search terms. Risk of bias in non-randomized studies - of intervention tool and Cochrane risk-of-bias tool for randomized trials were applied for risk of bias assessment. This review includes only severe pain defined as visual analogue scale or numeric rating scale (NRS) 7–10. Fifteen articles were included in this study. In general, pain intensity was reduced significantly after the intervention (MD -4.58; 95 %CI -5.25 to −3.91). However, subgroup analysis failed to identify any significant reduction in ganglion Impar group. Regarding morphine consumption, the intervention was significantly subsided the need of morphine (SMD -1.31; 95 %CI -1.86 to −0.76). In meta-regression, follow-up period was significantly moderated the pain changes by increasing 0.43 score within a month after the intervention (p value < 0.01). The limitation of this study lies on the pain assessment that used NRS which is a self-reported evaluation and may lead to self-reported bias. In conclusion, the sympathetic intervention demonstrates its effectiveness in cancer pain. However, since GI intervention mostly failed to reduce the pain severity during the follow up, GI intervention should be used in combination with another intervention.